Biophotonics Congress 2021 2021
DOI: 10.1364/brain.2021.bm3b.3
|View full text |Cite
|
Sign up to set email alerts
|

Implantable integrated photonic probe for light sheet brain imaging in vivo

Abstract: We present implantable silicon photonic probes for selective plane illumination imaging in vivo. The small form factor of the probes minimizes tissue displacement and heat dissipation while providing planar illumination from within the tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The light-sheet beam profile in fluorescein solution had a semi-uniform beam region covering an area >0.22 mm 2 and an FWHM sheet thickness of <16 μm up to 300 μm propagation distance in free space, slightly larger than the sheet thickness realized with another neural probe implemented with a single grating as the light-sheet emitter. 92 Optical sectioning in imaging could be achieved by sequentially addressing light to the 5 light-sheet emitters on the shanks with a vertical pitch of 78 μm. Each shank tip had a width of 60 μm and a thickness of 50–92 μm.…”
Section: Nanophotonic Neural Probesmentioning
confidence: 99%
“…The light-sheet beam profile in fluorescein solution had a semi-uniform beam region covering an area >0.22 mm 2 and an FWHM sheet thickness of <16 μm up to 300 μm propagation distance in free space, slightly larger than the sheet thickness realized with another neural probe implemented with a single grating as the light-sheet emitter. 92 Optical sectioning in imaging could be achieved by sequentially addressing light to the 5 light-sheet emitters on the shanks with a vertical pitch of 78 μm. Each shank tip had a width of 60 μm and a thickness of 50–92 μm.…”
Section: Nanophotonic Neural Probesmentioning
confidence: 99%
“…To study the brain circuitry, it is important to deliver light precisely to a small population of neurons deep in the brain. Silicon photonics can provide an implantable, precise, switchable light delivery system [ 17 , 92 , 93 , 94 ]. Mohanty et al demonstrated an implantable reconfigurable probe based on the SiN platform [ 17 ], as shown in Figure 13 a.…”
Section: Other Emerging Free-space Applicationsmentioning
confidence: 99%
“…The optical stimulation was combined with nearby tungsten electrodes to record the neuron activity. Implantable silicon photonic light delivery probes have also been used for fluorescence imaging [ 93 , 94 ]. For example, Sacher et al developed implantable probes to generate light-sheets deep in scattering tissues and demonstrated in vitro and in vivo fluorescence imaging of mouse brains [ 93 ].…”
Section: Other Emerging Free-space Applicationsmentioning
confidence: 99%